Respuesta :
Answer:
Step-by-step explanation:
The general equation of the slope intercept is y = mx + b.
Givens
m = 2
point: -3, - 6
Solution
Find the slope first
y = mx + b
y = 2x + b
Now use the fact that
- y = - 6
- x = - 3
-6 = 2*(-3) + b So you are solving for b
-6 = - 6 + b Add 6 to both sides.
-6 + 6 = -6+6 + b
b = 0
Final Answer
y = 2x
Answer:
y = 2x
Step-by-step explanation:
From question statement, we observe that
Slope and a point is given .We have to find the slope-intercept form of line.
Slope = 2 and (x,y) = (-3,-6)
y = mx+c eq(1)
is slope-intercept form of line where m is slope and c is y-intercept.
Putting given values in eq(1) , we have
-6 = (2)(-3)+c
-6 = -6+c
c = 0
Hence, y-intercept iszer0.
Putting the value of y-intercept and slope in eq(1), we have
y = (2)x+(0)
y = 2x is slope intercept form of line whose slope is 2 and passes through the point (-3,-6).